Gender Inequality from an Economic Perspective - Mallo, Rocío Paulina (2025)
This paper addresses economic inequality from a gender perspective, highlighting how the gender pay gap, the sexual division of labor, career choices constrained by "glass walls," and the invisibility of the care economy perpetuate economic disparities. Integrating gender perspectives into economic analysis is essential for questioning the role assigned to women in the economy by neoclassical economic theory, as well as for understanding and discuss the roots of these disparities. The research delves into the relationship between economic and gender inequality, evaluating factors such as the distribution of unpaid work and women's participation in the labor market. Additionally, it analyzes gender inequality indicators and presents a critical analysis of how labor market structures and social expectations limit leadership opportunities for women, negatively impacting economic development.